Exploring the Role of the Pharmacist in the Prevention and Management of Hypertensive Disorders in Pregnancy in Ashanti Region, Ghana - Pauline Boachie‐Ansah; Berko Panyin Anto; Afia Frimpomaa Asare Marfo; Edward Tieru Dassah; Morrison Asiamah; Ivan Eduku Mozu; Nana Ofori Adomako; Kwaku Gyamfi Oppong (The Journal of Clinical Hypertension)
ABSTRACT Hypertensive disorders in pregnancy (HDPs) are a leading cause of poor maternal and birth outcomes worldwide. Prompt management of these disorders is usually recommended to optimize outcomes. Administration of pharmacotherapeutic agents is critical in the prevention and management of these disorders. The services of the pharmacist are required to maximize the benefits of drug therapy during prevention and management. There is a paucity of data on the effectiveness of pharmacist‐led interventions in the management of these disorders in Ghana. This study investigated the effect of a pharmacist‐led intervention on knowledge, adherence to antihypertensive medication, and blood pressure (BP) control among pregnant women. A quasi‐experimental study was conducted. The study was carried out among pregnant women with moderate to high risk of developing HDPs and seeking antenatal care at a university hospital in Kumasi, Ghana. The pharmaceutical care model comprising health education, counseling, and medication administration reminders was provided fortnightly to study participants till delivery. Differences in pre‐ and post‐intervention median scores were compared using the Wilcoxon signed‐rank test. The mean age was 35.7 years (± 1.2). The overall median knowledge and adherence scores increased significantly after the intervention by 11 versus 17 (p < 0.001) and 5 versus 9 (p < 0.001), respectively. Pharmaceutical intervention increased the proportion of mothers who were adherent by 68.9% (95% CI, 53.9–83.8%; p < 0.001). The commonest side effect of the two first‐line antihypertensives (nifedipine and methyldopa) was headache. About 91% of the women delivered vaginally, and almost all (97.8%) of all deliveries were live births. Pharmacist‐led interventions had a positive impact on the knowledge of HDPs and adherence to antihypertensive medication in the study setting. Thus, incorporating pharmaceutical care into antenatal care would be worthwhile.